Financial, legal and administrative management of INCO-NET projects. Difficulties, solutions and recommendations for the future - Muñoz M.; Siller C.; Bossi M.; Le Meur F.; Pohl K. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
Since 2008, International Science and Technology Cooperation has become one of the major focus areas of the 7th Framework Programme. FP7 has been broadly opened to the participation of third countries and is aimed to promote political cooperation, dialogue and trust and to exemplify the free circulation of knowledge at a global level – the “Fifth Freedom”. However, although international cooperation has been strongly encouraged in the FP7 and many projects with an international component have been funded, the management of projects can become problematic if it is not sufficiently recognised and effectively supported. INCO-NET Projects include complex consortia where raising awareness of the FP7 management system is crucial; actually one of the main difficulties encountered in the management of these projects is directly linked to the existing differences within the European Commission’s system to manage FP7 projects, and to the internal administrative system of each beneficiary. This article aims to reflect on the main distinctions between the different systems, while proposing solutions and recommendations that could be taken into account for future International ST Cooperation projects.